Impact of external factors on determining E-commerce benefits among SMEs in Malaysia - Kartiwi, Mira; Hussin, Husnayati; Suhaimi, Mohd Adam; Mohamed Razi, Mohamed Jalaldeen; Ruhul, Amin (2018)
This paper examines how the external factors – i.e. customers, competitors – that driven Malaysian SMEs to adopt E-Commerce may influence the benefits these SMEs gained by adopting such technologies. The findings show the SMEs that were driven to adopt E-Commerce by customers demand are less likely to experience the reduction of operational cost. The results also show that SMEs would be able to achieve most of the expected benefits of E-Commerce adoption, if it is aimed as a tool to improve the competitiveness of the business.